2023
DOI: 10.1002/ps.7803
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial profile of the culturable olive sporobiota and its potential as a source of biocontrol agents for major phytopathogens in olive agriculture

Julia Manetsberger,
Natacha Caballero Gómez,
Nabil Benomar
et al.

Abstract: BACKGROUNDThe phytopathogens Xylella fastidiosa and Verticillium dahliae present an unparalleled threat to olive agriculture. However, there is no efficient field treatment available today for either pest. Spore‐forming bacteria (i.e., the sporobiota) are known for their extraordinary resistance properties and antimicrobial activity. The aim of this study was thus to identify potential novel sustainable spore‐forming biocontrol agents derived from the culturable olive microbiome, termed the sporobiota, in gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…simplex also reduced fungi-associated diseases in potato (pink rot) and wheat (Septoria Tritici Blotch) [65,66], while other studies demonstrated its antagonistic activity against the phytopathogens Pectobacterium sp. and Xylella fastidiosa [67,68]. Finally, in silico studies of the strain BA2H3 suggested the production of the antimicrobial compounds bacitracin and anthrachelin [67,74].…”
Section: Antimicrobial Activitymentioning
confidence: 97%
“…simplex also reduced fungi-associated diseases in potato (pink rot) and wheat (Septoria Tritici Blotch) [65,66], while other studies demonstrated its antagonistic activity against the phytopathogens Pectobacterium sp. and Xylella fastidiosa [67,68]. Finally, in silico studies of the strain BA2H3 suggested the production of the antimicrobial compounds bacitracin and anthrachelin [67,74].…”
Section: Antimicrobial Activitymentioning
confidence: 97%